Third Graders' Reading Proficiency Reading Texts Varying in Complexity and Length: Responses of Students in an Urban, High-Needs School. (December 2015) - Mesmer, Heidi Anne; Hiebert, Elfrieda H.
The Common Core State Standards for English Language Arts (CCSS/ELA) focus on building student capacity to read complex texts. The Standards provide an explicit text complexity staircase that maps text levels to grade levels. Furthermore, the Standards articulate a rationale to accelerate text levels across grades to ensure students are able to read texts in college and the workplace on high school graduation. This study empirically examined how third graders at two reading proficiency levels performed with texts of differing degrees of complexity identified as the Grades 2 to 3 band within the CCSS. The study also investigated the influence on comprehension of two text lengths. Results suggest that the compounding effects of text complexity and length uniformly affected reading proficiency of third graders. Typically, when presented with two texts of the same complexity level, readers had lower comprehension in the lengthier version of the text than the shorter version. Features of the single level where performances on texts of different lengths were not statistically significant are described, as are implications for educational practice and future research.